When do athletes benefit from cardiac genetic testing? - Semsarian, C.; Orchard, J.; Gray, B.; Orchard, J. (British Journal of Sports Medicine, 2020)
Genetic testing has had a major impact in many areas of medicine, including sports cardiology. Here we discuss cardiac genetic testing not as a screening tool but rather as an evidence-based follow-up test in an athlete with an abnormal ECG or medical history to identify those athletes who have a potentially life-threatening cardiac genetic disorder.